The Influence of Canva Application on the English Language Learning Outcomes Students of SMA Muhammadiyah Rappang - Syahrir L; Isumarni Isumarni; Nurul Faradillah; Nur Hikmah (La Ogi : English Language Journal, 2023)
The research entitled " The Influence of Canva Application on the English Language Learning Outcomes Students of SMA Muhammadiyah Rappang" was motivated by the absence of learning using the Canva application applied to Indonesian subjects, so there is a need for innovation in the use of learning media to create a pleasant learning atmosphere for students. This study aims to determine the effect of using the canva application on the learning outcomes of students of SMA Muhammadiyah Rappang. The instrument in this study used a multiple-choice test of 20 numbers. The sample in this study was 23 students of grade XI SMA Muhammadiyah. For data analysis techniques in this study using the mean formula. Based on the results of the study, in accordance with hypothesis testing through data analysis, the initial test score (Y) results were lower than the final test score (X), namely Y = 75.65 < X = 86.73. The difference in the results of these scores proves that the working hypothesis that states there is an influence on the use of canva on Indonesian the learning outcomes students of grade XI SMA Muhammadiyah Rappang is "accepted". While the null hypothesis that states "there is no effect of using canva on Indonesian the learning outcomes students of grade XI SMA Muhammadiyah Rappang is "rejected". Thus, it can be concluded that the use of canva in learning affects the Indonesian learning outcomes students of grade XI SMA Muhammadiyah Rappang.